Pengembangan Aplikasi Manajemen Litabmas Pendanaan Mandiri dengan Pendekatan Hierarchical Model-View-Controller (HMVC) - Wahyuni, Eka Dyar; Afandi, Mohamad Irwan; Putra, Agung Brastama (LPPM Universitas Bina Sarana Informatika, 2024)
In higher education, overseeing the execution of litabmas activities is a challenging and error-prone task, particularly when done manually through the physical submission of documents. Information is not always readily available, archives are frequently lost or even damaged, and tracing Litabmas external responsibility (articles, journals, patents/IPRs, etc.) from earlier periods can be challenging. This article describes how the Waterfall approach was used to construct the Litabmas management application. The Hierarchical Model-View-Controller (HMVC) technique is used to build the code architecture during the coding process. By reducing intermodular dependencies, this method makes it easier for a team to design an application. This application was developed to facilitate the management of the full cycle of Litabmas activity implementation for users, from generating Litabmas master data to initiating the Litabmas period, submitting proposals, conducting evaluations, and reporting Litabmas outputs and outcomes. The application has been tested using the black box method, and as a result, 23 use cases from six levels of users —administrator, head of institutional research, researcher, reviewer, auditor, and general visitor access rights —have been generated. All of these usecase have 100% of the expected output produced by the application.